Combined effects of waste bagasse ash and glass powder on the physical properties and compressive strength of construction bricks - Artbumrung, Siriwan; Srila, Must; Srisuwan, Anuwat; Saengthong, Chiawchan; Lawanwadeekul, Siwat; Sittiakkaranon, Sibpawishkon; Phonphuak, Nonthaphong (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
The present study focused on the physical properties and the compressive strength of fired clay bricks from combined waste bagasse ash (WBA) and glass powder (GP). Clay bricks were fabricated by incorporating WBA at 10, 20, 30, and 40 wt.% in clay mixture, while the constant GP powder was added to 10 wt.%. Green samples were then fired at 900, 1000, and 1100 oC. The influences of WBA and GP powder content on the physical properties and the compressive strength were determined. The results showed that an increase of WBA and GP powder content affected the improvement of the structural pores and compressive strength of the fired clay bricks. The fired clay brick should be required a compressive strength value of more than 17.2 MPa as per ASTM C62-13a, which was obtained in 10 wt.% WBA and GP content (17.85 MPa) after firing at 1100 oC. As a combined additive, the WBA and GP-powder could be imparted a synergistic effect in producing the sufficiently high strength fired clay brick. The use of wastes WAB and GP powder in manufacturing clay brick is an important step in reducing environmental pollution and protecting natural clay resources.